Berberine Attenuated Proliferation, Invasion and Migration by Targeting the AMPK/HNF4α/WNT5A Pathway in Gastric Carcinoma - Hu, Qian; Li, Lingli; Zou, Xin; Xu, Lijun; Yi, Ping (Frontiers in Pharmacology, 2018)
Background: Recent epidemiologic studies have found that patients with diabetes have a higher risk of gastric cancer(GC), and the long-term use of metformin is associated with a lower risk of gastric cancer. It is believed that blocking tumor energy metabolic alterations is now emerging as a new therapeutic approach of cancer. Berberine, a natural isoquinoline alkaloid, could modulate lipid metabolism and glucose homeostasis by regulating the expression of HNF4α in many metabolic diseases. Here, we investigated the effect of Berberine on GC and its possible molecular mechanism through targeting HNF4α. Methods and Results: (1) AGS and SGC7901 gastric cancer cells were treated with Berberine(BBR). We found that in AGS and SGC7901 cell, BBR inhibited cell proliferation through downregulating C-myc. BBR also induced G0-G1 phase arrest with the decreased expression of cyclin D1. Moreover, BBR attenuated the migration and invasion by downregulating MMP-3. (2) The lentivirus infection was used to silence the expression of HNF4α in SGC7901 cell. The results demonstrated that the knockdown of HNF4α in SGC7901 slowed cells proliferation, induced S phase arrest and dramatically attenuated gastric cancer cells’ metastasis and invasion. (3) We performed GC cells perturbation experiments through BI6015, AICAR, Compound C, metformin and BBR. Our findings indicated that BBR downregulated HNF4α while upregulating p-AMPK. Moreover, the inhibition of HNF4α by BBR was AMPK dependent. (4)Then the LV-HNF4α-RNAi SGC7901 cell model was used to detect the downstream of HNF4α in vitro. The results showed that the knockdown of HNF4α significantly decreased WNT5A and cytoplasmic β-catenin, but increased E-cadherin in vitro. Berberine also downregulated WNT5A and cytoplasmic β-catenin, the same as LV-HNF4α-RNAi and BI6015 in GC cells. (5) Finally, the SGC7901 and LV-HNF4α-RNAi SGC7901 mouse-xenograft model to evaluate the effect of BBR and HNF4α gene on GC tumor growth. The result illustrated that BBR and knockdown of HNF4α suppressed tumor growth and decreased HNF4α, WNT5A and cytoplasmic β-catenin levels. Conclusion: BBR had proliferation inhibition effect and attenuated the invasion and migration on GC cell lines, also suppressed the GC tumor growth in vivo. The anti-gastric cancer mechanism of BBR might be involved in AMPK-HNF4α-WNT5A signalling pathway.